Tinjauan Yuridis Akibat Hukum Perjanjian Harta Bersama yang Dibuat Oleh Suami Istri Setelah Perkawinan Berdasarkan Putusan Mahkamah Konstitusi Nomor 69/PUU-XIII/2015 - Abdul Hariss; Nurul Wulan Kasmara (Wajah Hukum, 2019)
A marriage is a commitment between two people, in this case a man and woman, with material purpose to build a happy and everlasting family (household) based on Belief in the one and only God which is the first principle of Pancasila(Five Principles). Asset/property issue may arise due to marriage. The development of society’s mindset lead them to enter into a prenuptial agreement before they get married considering that both husband and wife are able to earn asset/property. Besides that, there are many other reasons to enter into a prenuptial agreement. Basically there is no mixture of wealth in marriage between husband and wife. The bconcept of shared assets originally came from customsnor traditions that developed in indonesia. This concept is then suported by islamic law and positive laws that apply in our country. Then a joint proprty agreement was made.  Prenuptial Agreement is an agreement which is made by two people (betrothed couple) before they get married. Prenuptial Agreement had been stipulated in Article 29 Law No. 1 of 1974. However, since the Constitutional Court issued the Decision No. 69/PUU-XIII/2015, Prenuptial Agreement has several modifications which are presently being pros and cons in society. The matter which is being researched in this thesis is: what is the legal consequence of a prenuptial agreement which is made after marriage and based on the Decision of Constitutional Court No. 69/PUU-XIII/2015. The approach method which is used herein is normative legal research. The law material sources are primary law material and secondary law material in form of books and Legislation. Data analyses used in this research are processing and analyzing the data qualitatively andthen descriptively drawn up. The result of this research found the differences between Prenuptial Agreement which is stipulated in Article 29 Law No. 1 of 1974 and the Prenuptial Agreement which is stipulated in the Decision of Constitutional Court No. 69/PUU-XIII/2015